An Academic Library Utilization of Research Guides to Disseminate Consumer Health Resources. Issue 4 (1st October 2020) - Kirkpatrick, Niki; Dixson, Melanie A.
Abstract: The University of Tennessee, Knoxville Libraries (UT Libraries) utilizes research guides as supplemental training resources, educational tools, and community enrichment aids to support health literacy. This article illustrates case studies of three UT Libraries research guides that provide consumer health information, breaking down each research guide's development, facilitation, and purpose. As a training resource, the Cultural Competency Guide works to support the course curriculum. The Introduction to Health Sciences Research Guide serves as an educational tool by establishing foundational information for consumer health assimilation. Lastly, the Seed Library & Gardening Guide serves as a community enrichment aid to encourage healthy lifestyles and share food insecurity information that impacts campus and local communities.